2011
DOI: 10.2341/10-107-lr1
|View full text |Cite
|
Sign up to set email alerts
|

Marginal, Internal Fit and Microleakage of Zirconia Infrastructures: An In-Vitro Study

Abstract: This in-vitro study compared the marginal and internal fit and also the microleakage of zirconia infrastructures (Procera All-Zircon, Cercon Smart Ceramics) in contrast to heat-pressed ones (Empress 2).Thirty maxillary premolars (n=30) were divided into three groups (n=10) and prepared with individual chamfer preparations by using the silicone index method. Plaster dies of 10 individual preparations were allocated to each coping fabrication method of computer-aided design and computer-aided manufacturing (Proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 30 publications
1
20
1
4
Order By: Relevance
“…For the manual adapted copings, the mean marginal gaps varied from 54 to 59.9 μm. This is in accordance with marginal gaps reported for CAD/ CAM-generated zirconia copings in other studies, in which marginal gaps ranged from 24 to 110 μm 6,11,14,15,31) . The large variation in the reported mean values can be explained by a number of infl uencing factors, including CAD/CAM components and differences between presintered and post-sintered milling of the zirconia blank.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For the manual adapted copings, the mean marginal gaps varied from 54 to 59.9 μm. This is in accordance with marginal gaps reported for CAD/ CAM-generated zirconia copings in other studies, in which marginal gaps ranged from 24 to 110 μm 6,11,14,15,31) . The large variation in the reported mean values can be explained by a number of infl uencing factors, including CAD/CAM components and differences between presintered and post-sintered milling of the zirconia blank.…”
Section: Discussionsupporting
confidence: 93%
“…The large variation in the reported mean values can be explained by a number of infl uencing factors, including CAD/CAM components and differences between presintered and post-sintered milling of the zirconia blank. In in vitro studies using the same CAD/CAM system (Cercon) such as the present study, mean values for marginal openings were reported to range from 38 to 66 μm 11,27,31) . The variation in reported mean values of samples derived from the same CAD/CAM system can be explained by differences in study designs and measurement techniques, including evaluations of cemented or non-cemented crowns; various preparation designs of abutments; different types of microscope/ magnifi cations used for the measurements; and the location and quantity of single measurements 6) .…”
Section: Discussionmentioning
confidence: 51%
“…Penetration of the dye depends on molecular size of the dye, molecular polarity, surface interface and time. Both dye and ink penetration provides a similar sealing ability [33]. In the present study, no significant difference in the vertical marginal gap values were found between the two tested groups before or after thermocycling.…”
Section: Discussioncontrasting
confidence: 42%
“…In order to assess microleakage, all teeth were covered with nail polish varnish apical to the margin of the restoration by 1 mm to prevent any dye penetration except at the tooth/crown interface. Then, the teeth were immersed in 0.5% basic fuchsin dye for 48 hours [33] at 37°C. By using Isomet saw (Buehler Isomet saw 4000), the crowns were sectioned vertically in a buccolingual direction with low-speed cutting saw of 0.7 mm thickness abrasive disc, at speed of 2500 rpm, under continuous watercoolant.…”
Section: Leakage Measurementmentioning
confidence: 99%
“…Based on these limited data, it can be concluded that the type of ceramic material could be effective on marginal gap, and IPS e.max ceramic material might have a smaller marginal gap as compared to zirconia; however, using a CEREC extraoral scanner, posterior restorations with shoulder preparation showed 29.98 μm and 13.15 μm marginal gap using glass‐infiltrated zirconia‐toughened alumina (In‐Ceram Zr) and tetragonal zirconia (In‐Ceram YZ), respectively . In posterior restorations using a Cercon extraoral scanner, 43 μm and 70 μm marginal gaps were reported using zirconia cores.…”
Section: Discussionmentioning
confidence: 99%